1991
DOI: 10.1016/0020-7292(91)90229-x
|View full text |Cite
|
Sign up to set email alerts
|

Cervical dysplasia in the postmenopausal female: diagnosis and treatment

Abstract: Thirty-two postmenopausal women, age 50 years or older, were colposcoped for abnormal Papanicolaou (PAP) smears. Sixteen had mild to moderate dysplasia, six severe dysplasia and the remainder had no dysplasia. Treatment included observation, topical estrogen, cryotherapy, conization or hysterectomy. Based upon our observations, satisfactory colposcopy can be performed in the majority of postmenopausal women. Oral or topical estrogen is a valuable adjunct in the initial evaluation and treatment of abnormal PAP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…With an ageing population, more post-menopausal women are presenting for cervical screening, and the smears of elderly women often cause cytodiagnostic problems 9 . In this study of 555 smears with post-menopausal atypia only these 16 (2.9%) finally showed histologically confirmed abnormal changes and 15 smears out of these 16 showed Ki-67 positivity.…”
Section: Discussionmentioning
confidence: 99%
“…With an ageing population, more post-menopausal women are presenting for cervical screening, and the smears of elderly women often cause cytodiagnostic problems 9 . In this study of 555 smears with post-menopausal atypia only these 16 (2.9%) finally showed histologically confirmed abnormal changes and 15 smears out of these 16 showed Ki-67 positivity.…”
Section: Discussionmentioning
confidence: 99%
“…18 Teaff et al reported that 5 of 12 (41.6%) postmenopausal women with minimally abnormal cytology (Pap smear class II) had biopsy-proven dysplasia. 21 From these studies, the reported frequency of underlying dysplasia in a postmenopausal women seems to vary significantly, from 5.6% to 41.6%. 17,18,21 Possible explanations for this variability include the small number of patients studied and, in the case of Teaff's study, the fact that ASCUS had not yet been defined as a separate diagnostic category.…”
Section: Discussionmentioning
confidence: 99%
“…21 From these studies, the reported frequency of underlying dysplasia in a postmenopausal women seems to vary significantly, from 5.6% to 41.6%. 17,18,21 Possible explanations for this variability include the small number of patients studied and, in the case of Teaff's study, the fact that ASCUS had not yet been defined as a separate diagnostic category. Our study of women older than 55 determined the incidence of ASCUS and the frequency of SIL following the diagnosis of ASCUS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,19,23 Although abnormal Pap smears are reported more frequently in postmenopausal women when compared to younger women, 12,13 the frequency of underlying dysplasia in the elderly population seems to vary significantly. Several groups have reported a high incidence of dysplasia and carcinoma on cervicovaginal smears and biopsies in postmenopausal women, 13,15,24 while others have found that squamous atypia in postmenopausal women is rarely associated with either biopsy-proven dysplasia or human papillomavirus (HPV) DNA detection, 5,20,23 and it is generally thought that the incidence of biopsy proven intraepithelial lesions decreases markedly after menopause. 14 In review of atypical atrophic cervicovaginal smears, Kaminski et al 9 concluded that there was a strong correlation between estrogen deficiency and squamous atypia.…”
Section: (14%) Showed Squamous Intraepithelial Lesion (Sil) and Atypimentioning
confidence: 99%